1991
DOI: 10.2135/cropsci1991.0011183x003100060018x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity and Associations of Some Potentially Drought‐responsive Characters in Durum Wheat

Abstract: Genetic improvement of crop plants for drought resistance is hindered by lack of information on variability and associations of drought‐response characters in breeding materials. We evaluated 3430 accessions in a world collection of durum wheat (Triticum turgidum L. var. durum) for 19 characters under severe moisture‐limiting field conditions at Swift Current, SK, Canada in 1984. Phenotypic diversity (H) and multicharacter associations were investigated in germplasm from nine durum wheat growing regions. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…The leaf samples were weighted (W1), wilted for 2 hour at 35oC, reweighed (W2), and oven-dried for 48 h at 70 o C to obtain dry weight (W3). The RWL was calculated using the following formula (Yang et al 1991):…”
Section: Methodsmentioning
confidence: 99%
“…The leaf samples were weighted (W1), wilted for 2 hour at 35oC, reweighed (W2), and oven-dried for 48 h at 70 o C to obtain dry weight (W3). The RWL was calculated using the following formula (Yang et al 1991):…”
Section: Methodsmentioning
confidence: 99%
“…Positive correlations between number of heterozygous allozyme loci and fitness-related traits have been reported (e.g., Ledig et al 1983;Linhart and Mitton 1985;Strauss 1986), but other studies showed either no or negative correlations (e.g., Bush et al 1987;Linhart et al 1989). The existence of gene co-adaptation in such studies can cause this inconsistency; for example, a fitness-related trait such as drought-response is controlled by a block of co-adapted gene complexes in some species (Yang et al 1991).…”
Section: New Computer Programsmentioning
confidence: 99%
“…Similarly, there is a growing body of data on biochemical and molecular genetic variation, which is also underutilised. With the application of analytical techniques recently developed at the University of Alberta (e.g., Yang et al 1991, Yang et al 1996, quantitative and biochemical/molecular data can provide much more valuable information on population genetic structure, thus promoting the development of more effective conservation strategies, and the acceleration of genetic improvement programmes.…”
Section: New Computer Programsmentioning
confidence: 99%
“…The minimum value of the index was zero for a uniform population. The value of the index increases with increase within population variability and reaches maximum value when all phenotypic classes have equal frequencies (Yang et al, 1991). To test for the differences among pairs of Ĥ' values at P< 0.05, a t-statistic according to Jain et al (1975) was used as given by the formula:…”
Section: Morphological Data Analysismentioning
confidence: 99%